KARAKTERISTIK UJI IMPAK (IMPACT TEST) CHARPY PAPAN KOMPOSIT BERBAHAN SERAT TANDAN KOSONG KELAPA SAWIT DIPERKUAT SERAT KACA - Sarumpaet, Josafat; Mahyunis, Mahyunis; Zakwan, Zakwan (Institut Teknologi Sawit Indonesia (ITSI), 2021)
Oil palm empty bunches (TKKS) are solid waste from palm oil processing which is quite large and until now its utilization is still not optimal. Therefore, it is necessary to innovate the processing technology of oil palm empty bunches in order to produce products that have more usefulness and high economic value as well. One of the processed products from the solid waste of oil palm empty bunches is composite. By utilizing solid waste of oil palm empty bunches (EFB) to be used as a base material for making (filler) and BTQN 157 EX resin as a matrix, catalysts as hardeners and glass fibers (fiberglass) as reinforcement are expected to produce composite boards that have proven quality by testing. impact standard ASTM E23. This research was conducted at the STIPAP TPHP Laboratory and the Laboratory of Basic Phenomena of Mechanical Engineering, the Medan Institute of Technology (ITM). The research period was 2 months, namely July - August 2019. This research used handmade methods and charphy impact testing with a composition of 29% OPEFB fiber, 157 ex 70% BTQN resin, 1% catalyst and glass fiber. The results showed that the average absorption energy of the 8 samples was 0.833 Joules and the average impact price was 0.0108 joules / mm2.